Developing STEM-integrated augmented reality learning media for smart ship engine monitoring systems: Enhancing marine engineering competency in Indonesian maritime vocational education - Tri Kismantoro; Nazilul Hamidi; Rosna Yuherlina Siahaan (Journal of Advanced Sciences and Mathematics Education, 2025)
Background: The transition toward Maritime Industry 4.0 requires maritime vocational institutions to integrate smart ship technologies into their curricula. This shift demands innovative pedagogical approaches that merge STEM principles with immersive tools such as Augmented Reality (AR) to strengthen competencies in intelligent engine monitoring systems in accordance with STCW standards. Aim: This study investigates the extent to which STEM-integrated AR learning media supports the development of marine engineering competencies among Indonesian maritime vocational students, and how such contributes to evidence-based instructional frameworks for technology-enhanced maritime education. Method: A qualitative interpretive phenomenological approach was implemented over sixteen weeks involving twenty-five marine engineering students, six instructors, and five industry experts. Data were collected through semi-structured interviews, systematic observations, and weekly reflection journals, and analyzed using Braun and Clarke’s thematic analysis. Results: Five learning themes were identified: transformative visualization, authentic STEM integration, increased technological self-efficacy, collaborative knowledge construction, and contextual implementation challenges. Competency assessments showed notable gains, with MECAI scores reaching cognitive (84.2%), psychomotor (81.6%), affective (86.9%), and digital literacy (87.3%) domains. STEM Integration Effectiveness also demonstrated strong technology (85.4%) and engineering (81.7%) performance. Conclusion: The findings validate AR-enhanced STEM learning as an effective approach for strengthening STCW-aligned competencies and offer context-sensitive guidance for maritime institutions, particularly those operating under resource limitations.